Making AI an ally for sustainable agriculture in the face of climate change - Lalit Gautam (Field Actions Science Reports)
Climate change is profoundly reshaping socio-economic structures worldwide, posing challenges to various sectors, especially agriculture. The agricultural industry is particularly vulnerable to unpredictable weather patterns, increased extreme events and the degradation of natural resources. These disruptions threaten food production, global food security, economic stability and community livelihoods. As agriculture both influences and is affected by climate change, it is crucial to develop and implement solutions that address these complex issues to foster resilience and sustainability. This article explores the role of technology and artificial intelligence (AI) in mitigating the effects of climate change on agriculture. By examining the sector’s challenges, the article highlights the importance of data and technological innovation in transforming agricultural practices, particularly in developing countries. Through the innovative work of SenseGrass, it illustrates how AI-driven solutions are transforming farming, enhancing sustainability and building climate resilience. Based on examples from the industry, this article provides a glimpse into the future, demonstrating AI's potential to drive positive change not only in agriculture, but also in addressing broader issues posed by climate change.